1996
DOI: 10.1038/ng0496-448
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Fac in mice produces inducible chromosomal instability and reduced fertility reminiscent of Fanconi anaemia

Abstract: Fanconi anaemia (FA) is an autosomal recessive disease characterized by bone marrow failure, variable congenital malformations and predisposition to malignancies. Cells derived from FA patients show elevated levels of chromosomal breakage and an increased sensitivity to bifunctional alkylating agents such as mitomycin C (MMC) and diepoxybutane (DEB). Five complementation groups have been identified by somatic cell methods, and we have cloned the gene defective in group C (FAC)(7). To understand the in vivo rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
154
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(164 citation statements)
references
References 18 publications
10
154
0
Order By: Relevance
“…We and others have previously created strains of mice with targeted deletions of the murine Fanca, Fancc, and Fancg genes, all components of the FA nuclear complex. These mutants have very similar phenotypes (Chen et al 1996;Whitney et al 1996;Cheng et al 2000;Yang et al 2001;Koomen et al 2002;Noll et al 2002), supporting a model in which the components of the complex participate in a common function. To determine whether Fancd2 participates only in this function in vivo or has additional roles, we generated a strain of mice with a null allele in this gene.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…We and others have previously created strains of mice with targeted deletions of the murine Fanca, Fancc, and Fancg genes, all components of the FA nuclear complex. These mutants have very similar phenotypes (Chen et al 1996;Whitney et al 1996;Cheng et al 2000;Yang et al 2001;Koomen et al 2002;Noll et al 2002), supporting a model in which the components of the complex participate in a common function. To determine whether Fancd2 participates only in this function in vivo or has additional roles, we generated a strain of mice with a null allele in this gene.…”
Section: Discussionmentioning
confidence: 59%
“…Knockouts of Fancc (Chen et al 1996;Whitney et al 1996), Fanca (Cheng et al 2000;Noll et al 2002), and Fancg (Yang et al 2001;Koomen et al 2002) all share a defect in germ-cell development and demonstrate cellular sensitivity to agents that produce DNA interstrand cross-links (ICLs). In contrast to human FA patients, however, FA mice do not develop anemia and do not have skeletal defects; nor are they at an increased risk for developing cancer.…”
mentioning
confidence: 99%
“…In other monozygotic twins with different phenotypes somatic mosacism was not detected. Additionally, in mouse models of Fanconi anaemia, in which somatic mosacism is not possible by virtue of both alleles carrying identical deletions, there is also a variable penetrance of the phenotype [18][19][20][21][22][23][24][25][26][27]. Hence, there is a stochastic element that contributes to the severity of the phenotype that is likely to be due to an endogenous or exogenous source of DNA damage.…”
Section: Fa Is Genetically Complexmentioning
confidence: 99%
“…In fact, all FA mouse models to date exhibit the same fertility defect [18][19][20][21][22][23][24][25][26][27]. FA mutant mice are born with extremely few germ cells in either the testis or the ovary.…”
Section: Developmental Abnormalitiesmentioning
confidence: 99%
“…3 Recent experimental studies showed that in animal models of FA, such as Fancg/Xrcc9 null mice or mice mutant for FA complementation group C, the number of germ cells was dramatically reduced, suggesting that FA complementation groups are required for mitotic proliferation of primordial germ cells. [4][5][6] However, the pathophysiology of ovarian failure has not been clearly elucidated in human females and no histo-pathologic study has been published. Causes may be multifactorial, as suggested by some FA patients presenting with hypergonadotropic hypogonadism caused by germ cell insufficiency, with or without associated pituitary stalk interruption.…”
mentioning
confidence: 99%